Extra-forebrain impact of antipsychotics indicated by c-Fos or FosB/ΔFosB expression: A minireview - Kiss Alexander; Osacka Jana (Endocrine Regulations, 2021)
It is apparent that the c-Fos and FosB/ΔFosB immunohistochemistry has generally become a useful tool for determining the different antipsychotic (AP) drugs activities in the brain. It is also noteworthy that there are no spatial limits, while to the extent of their identification over the whole brain axis. In addition, they can be in a parallel manner utilized in the unmasking of the brain cell phenotype character activated by APs and by this way also to identify the possible brain circuits underwent to the APs action. However, up to date, the number of APs involved in the extra-striatal studies is still limited, what prevents the possibility to fully understand their extra-striatal effects as a complex as well as differentiate their extra-striatal impact in qualitative and quantitative dimensions. Actually, it is very believable that more and more anatomical/functional knowledge might bring new insights into the APs extra-striatal actions by identifying new region-specific activities of APs as well as novel cellular targets affected by APs, which might reveal more details of their possible side effects of the extra-striatal origin.